2009
DOI: 10.1051/dst/2009019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Ca/P molar ratio on the quantity and crystalline structure of calcium phosphates obtained from aqueous solutions

Abstract: et al.. Effects of pH and Ca/P molar ratio on the quantity and crystalline structure of calcium phosphates obtained from aqueous solutions.Abstract -Milk and dairy products contain large amounts of calcium phosphate salts that can precipitate. The chemical composition and the crystalline structure of the calcium phosphate precipitates that are formed in dairy industry depend on the physico-chemical conditions, particularly, pH and mineral composition. The objective of this study was to determine, using mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 30 publications
7
70
0
1
Order By: Relevance
“…The formation of calcium phosphate precipitates depends on environmental conditions such as pH, ionic strength, temperature, molar ratio of Ca/P, presence of other ions (Johnsson & Nancollas, 1992;Schmidt, Both, Visser, Slangen, & Vanrooijen, 1987;Spanos et al, 2007;Van Kemenade & De Bruyn, 1987). Earlier studies (Johnsson & Nancollas, 1992;Mekmene et al, 2009;Van Kemenade & De Bruyn, 1987) have shown that pH is the key factor that determines the crystalline structure of calcium phosphates. DCPD and OCP are formed in more acidic conditions, whereas HAP is preferentially formed under neutral or basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of calcium phosphate precipitates depends on environmental conditions such as pH, ionic strength, temperature, molar ratio of Ca/P, presence of other ions (Johnsson & Nancollas, 1992;Schmidt, Both, Visser, Slangen, & Vanrooijen, 1987;Spanos et al, 2007;Van Kemenade & De Bruyn, 1987). Earlier studies (Johnsson & Nancollas, 1992;Mekmene et al, 2009;Van Kemenade & De Bruyn, 1987) have shown that pH is the key factor that determines the crystalline structure of calcium phosphates. DCPD and OCP are formed in more acidic conditions, whereas HAP is preferentially formed under neutral or basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with those obtained by Anema (2009) on industrial MDCP precipitates. In previous study, we showed the formation of poorly crystallised calcium deficient apatites (CDA) from aqueous solutions containing Ca and P i ions (Mekmene et al. 2009a).…”
Section: Resultsmentioning
confidence: 99%
“…1977; Madsen and Thorvardarson 1984; Nancollas 1990; Madsen and Christensson 1991; Guo et al. 2005; Mekmene et al. 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this can be the strong basic character of β-tricalcium phosphate, which can cause a change in the pH of the simulated body fluid in the vicinity of the tricalcium phosphate (TCP) particles. Furthermore, it is well known that the solubility of the calcium phosphates decreases at higher pH [55]. Thus, if the pH is high enough in the nearly supersaturated solution, spontaneous crystal formation can occur even if the sintered silica aerogel matrix reduces the number of the calcium binding sites.…”
Section: Discussionmentioning
confidence: 99%